Structural design and sand-discharge performance of the end-face groove of a cone bit. (April 2022) - Zhou, Yi; Jiang, Yang; Huang, Yuxing; Hu, Jiahao; Zhang, Wan; Tang, Yifeng
Highlights: Aiming at the seal wear, a new end face sand discharge structure was designed. The feasibility of the new structure is verified by numerical simulation. The influence of groove structure parameters on the performance is obtained. The structural parameters of the end face groove are optimized. Abstract: The sealing system of the roller cone bit indirectly determines the overall service life of the bit. However, the sealing part is one of the most easily damaged components of the roller cone bit. It can improve the sealing performance and service life of the bit and reduce the times of tripping during drilling. According to the results of the sealing failure analysis and the end-face position of the cone, the function of the end-face groove structure is defined as expelling most of the rock debris particles from the end face of the cone. The end-face sand-discharge structure is designed through theoretical analysis. Simulations are performed to study the performance of the end-face sand-discharge structure, verify the feasibility of the end-face sand-discharge structure, and obtain the effects of the structural parameters of the end-face sand-discharge structure on the performance of the structure. In the process, a new method of discrete phase particle tracking using simulation software is explored.